2013
DOI: 10.1002/prep.201200144
|View full text |Cite
|
Sign up to set email alerts
|

On AlO Emission Spectroscopy as a Diagnostic in Energetic Materials Testing

Abstract: The emission of AlO is commonly observed in tests involving aluminum combustion in propellants and explosives. Such emission has been used as a signature of combustion, as a tool for measuring ignition and reaction times, and as a thermometer. This paper provides a critical review of methodologies exploiting AlO emission spectroscopy as a quantitative tool in energetics testing. Controlled tests involving aluminized explosives, as well as those using added alumina, are conducted, in which AlO emission is quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2014
2014
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(12 citation statements)
references
References 59 publications
(84 reference statements)
1
10
0
1
Order By: Relevance
“…Previous studies also showed the predominance of AlO emission when Al plasma interacted with ambient air, which is consistent with the standard heat of formation being strongly exothermic for AlO and strongly endothermic for AlN[40]. During Al combustion, other molecules such as Al 2 O and AlO 2 can also be formed as intermediates, but they do not have strong emission bands in the visible region and are therefore not observed in this experiment[41].…”
supporting
confidence: 89%
“…Previous studies also showed the predominance of AlO emission when Al plasma interacted with ambient air, which is consistent with the standard heat of formation being strongly exothermic for AlO and strongly endothermic for AlN[40]. During Al combustion, other molecules such as Al 2 O and AlO 2 can also be formed as intermediates, but they do not have strong emission bands in the visible region and are therefore not observed in this experiment[41].…”
supporting
confidence: 89%
“…Note that different optical signatures, e.g., pulses filtered to select the AlO molecular emission or, alternatively, as is done here, focusing on the black body radiation, may have different durations and thus imply different absolute burn times (Peuker et al, 2013). Currently, there is no preferred method that can be used universally, so care should be taken when comparing burn times reported in studies using different optical signatures of the burning particles.…”
Section: Particle Burn Timesmentioning
confidence: 93%
“…The present results, however, indicate that strong multiple scattering of the light in two-phase metal flames makes spatial interpretation of the emission spectra unreliable. At best, the emission measurements can only indicate the maximum temperature in the flame, since emission intensity is strongly weighted to higher temperatures [25].…”
Section: Molecular Emission Spectra Of Alomentioning
confidence: 99%